THE APPLICATION OF USING GEL PAD AS A MEDIUM FOR ULTRASOUND SHOULDER - Sisparwati, Lelly Agustina; Setiawati, Rosy; Putri, Berliana Devianti (Faculty of Vocational Studies, Universitas Airlangga, 2020)
Background: A conductive medium on ultrasound is a medium that is used to obtain sound wave transmission by minimizing air between the transducer and the skin. This study used materials that are easily found such as gel wax and paraffin for making the gel pad. A good oil and mineral based wax gel are used as a basic ingredient for ultrasound gel making. Gel pad can be used to minimize the structure of unauthorized organs. One of which is the shoulder. Purpose: This study aims to determine the quality of the image in the use of standard gel, and the use of gel pad as a medium for ultrasound shoulder. Method: Gel pad is made by mixing gel wax and paraffin ingredients. This gel is used to obtain images from ultrasound investigation. The study used 16 samples with a total of 64 images obtained in which 32 images using standard gel and gel pad in the long axis position and 32 images using standard gel and gel pad in the short axis position. The analysis of image results is done using matlab image processing to assess SNR. The image quality obtained from the results of the questionnaire was assessed by a specialist in radiology. Image quality processing based on SNR was tested using independent T test. Meanwhile, the results of image quality from the questionnaire assessment were tested using Wilcoxon. Result: As many as 64 objects were obtained using standard gel. The gel pad showed that there were significant differences in the results of image quality based on SNR values. In the results of the questionnaire assessment, there are several anatomic organs that have no significant differences. Conclusion: The use of standard gel was still higher compared to the use of gel pad. The gel pad is able to become a standard gel alternative on ultrasound shoulder examination.